Companions to Kepler giant stars: a long-period eccentric sub-stellar companion to KIC 3526061 and a stellar companion to HD 187878 - Karjalainen, Marie; Karjalainen, Raine; Hatzes, Artie P.; Lehmann, Holger; Kervella, Pierre; Hekker, Saskia; Winckel, Hans Van; Überlauer, Jakub; Vítková, Michaela; Skarka, Marek; Kabáth, Petr; Prins, Saskia; et al. (Astronomy and astrophysics, 2022)
Context. Our knowledge of populations and the occurrence of planets orbiting evolved intermediate-mass stars is still incomplete. In 2010 we started a planet search programme among 95 giant stars observed by the Kepler mission to increase the sample of giant stars with planets and with reliable estimates of stellar masses and radii.Aims. We present the two systems from our planet search programme whose companions we were able to characterise: KIC 3526061 and HD 187878.Methods. We used precise stellar radial velocity measurements taken with four different echelle spectrographs to derive an orbital solution. We used Gaia astrometric measurements to obtain the inclination of the HD 187878 system and Kepler photometric observations to estimate the stellar mass and radius.Results. We report the discovery of a sub-stellar companion and a stellar companion around two intermediate-mass red giant branch stars. KIC 3526061 b is most likely a brown dwarf with a minimum mass of 18.15 ± 0.44 MJupiter in a long-period eccentric orbit, with orbital period d and orbital eccentricity e = 0.85 ± 0.01. It is the most evolved system found having a sub-stellar companion with such a high eccentricity and wide separation. HD 187878 B has a minimum mass of 78.4 ± 2.0 MJupiter. Combining the spectroscopic orbital parameters with the astrometric proper motion anomaly, we derived an orbital inclination deg, which corresponds to the companion’s mass in the stellar regime of .Conclusions. A sub-stellar companion of KIC 3526061 extends the sample of known red giant branch stars with sub-stellar companions on very eccentric wide orbits, and might provide a probe of the dynamical evolution of such systems over time.